Bioactive glass fillers reduce bacterial penetration into marginal gaps for composite restorations. Issue 1 (January 2016) - Khvostenko, D.; Hilton, T.J.; Ferracane, J.L.; Mitchell, J.C.; Kruzic, J.J.
Highlights: Novel bioreactor system was used for in vitro cyclic loading of tooth filling samples. We grew biofilms on simulated tooth restorations with bioactive and control composites. Bacteria penetrated less into marginal gaps for the bioactive glass containing samples. Bioactive glass fillers may have promise for slowing secondary caries formation. Abstract: Objective: Bioactive glass (BAG) is known to possess antimicrobial and remineralizing properties; however, the use of BAG as a filler for resin based composite restorations to slow recurrent caries has not been studied. Accordingly, the objective of this study was to investigate the effect of adding 15 wt% BAG to a resin composite on bacterial biofilms penetrating into marginal gaps of simulated tooth fillings in vitro during cyclic mechanical loading. Methods: Human molars were machined into approximately 3 mm thick disks of dentin and 1.5–2 mm deep composite restorations were placed. A narrow 15–20 micrometer wide dentin-composite gap was allowed to form along half of the margin by not applying dental adhesive to that region. Two different 72 wt% filled composites were used, one with 15 wt% BAG filler (15BAG) and the balance silanated strontium glass and one filled with aerosol silica and silanated strontium glass without BAG (0BAG—control). Samples of both groups had Streptococcus mutans biofilms grown on the surface and were tested inside a bioreactor for two weeks while subjected to periods of cyclic mechanical loading. After post-test biofilm viability was confirmed, each specimen was fixed in glutaraldehyde, gram positive stained, mounted in resin and cross-sectioned to reveal the gap profile. Depth of biofilm penetration for 0BAG and 15BAG was quantified as the fraction of gap depth. The data were compared using a Student's t -test. Results: The average depth of bacterial penetration into the marginal gap for the 15BAG samples was significantly smaller (∼61%) in comparison to 0BAG, where 100% penetration was observed for all samples with the biofilm penetrating underneath of the restoration in some cases. Significance: BAG containing resin dental composites reduce biofilm penetration into marginal gaps of simulated tooth restorations. This suggests BAG containing composites may have the potential to slow the development and propagation of secondary tooth decay at restoration margins.